Age-related hearing impairment and the triad of acquired hearing loss - Yang, Chao-Hui; Schrepfer, Thomas; Schacht, Jochen (Frontiers in Cellular Neuroscience, 2015)
Understanding underlying pathological mechanisms is prerequisite for a sensible design of protective therapies against hearing loss. The triad of age-related, noise-generated, and drug-induced hearing loss ¬¬displays intriguing similarities in some cellular responses of cochlear sensory cells such as a potential involvement of reactive oxygen species and apoptotic and necrotic cell death. On the other hand, detailed studies have revealed that molecular pathways are considerably complex and, importantly, it has become clear that pharmacological protection successful against one form of hearing loss will not necessarily protect against another. This review will summarize pathological and pathophysiological features of age-related hearing impairment (ARHI) in human and animal models and address selected aspects of the commonality (or lack thereof) of cellular responses in ARHI to drugs and noise.